Efficacy of indigenous Trichoderma isolates for the management of cumin wilt (Fusarium oxysporum f. sp. cumini) in Rajasthan - S Sriram, B Ramanujam, Y K Sharma, K Kant, (Journal of Spices and Aromatic Crops, 2014)
Sixteen Trichoderma isolates from soils under cumin, identified as Trichoderma harzianum, T. koningiopsis and T. asperllum showed variation in their colony morphology as well as degree of inhibition of Fusarium oxysporum f.sp. cumini. In the field experiment, all Trichoderma isolates were tested as seed treatment and soil application on cumin cultivar RZ 209. The result showed that T. asperllum (CuTa7-02, CuTa3-01), T. koningiopsis (CuTk7-01) and T. harzianum (CuTh9-02, CuTh3-03, CuTh8-01) significantly reduced wilt incidence (58-85%) and can be used as biological components in integrated management of cumin Fusarium wilt.